Heat transfer and single-phase flow in internally grooved tubes - Aroonrat, K.; Jumpholkul, C.; Leelaprachakul, R.; Dalkilic, A. S.; Mahian, O.; Wongwises, S. (PERGAMON-ELSEVIER SCIENCE LTD, 2013)
This study investigates heat transfer and flow characteristics of water flowing through horizontal internally grooved tubes. The test tubes consisted of one smooth tube, one straight grooved tube, and four grooved tubes with different pitches. All test tubes were made from type 304 stainless steel. The length and inner diameter of the test tube were 2 m and 7.1 mm, respectively. Water was used as working fluid, heated by DC power supply under constant heat flux condition. The test runs were performed at average fluid temperature of 25 degrees C, heat flux of 3.5 kW/m(2), and Reynolds number range from 4000 to 10,000. The effect of grooved pitch on heat transfer and pressure drop was also investigated. The performance of the grooved tubes was discussed in terms of thermal enhancement factor. The results showed that the thermal enhancement factor obtained from groove tubes is about 1.4 to 2.2 for a pitch of 0.5 in.; 1.1 to 13 for pitches of 8, 10, and 12 in., respectively; and 0.8 to 0.9 for a straight groove. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Nusselt number; Friction factor; Grooved tube; Type 304 stainless steel; PRESSURE-DROP; CONDENSATION; EVAPORATION; Thermodynamics; Mechanics